Uncharted Territory: towards an Evidence-Based Criminology of Sovereign Citizens Through a Systematic Literature Review - Fiebig, Verena (Perspectives on terrorism, 2022)
Sovereign citizens are part of an extreme anti-government movement. Since they fundamentally reject the authority of the state, they repeatedly come into conflict with governmental actors. Many publications have examined ideology and strategies of sovereign citizens. However, few studies empirically address their demographics and criminogenic factors. Based on a systematic literature review, we identified only eight empirical studies, which are used as the basis for this article’s assessments. The results of the systematic literature review provide information about empirical results on demographics, driving factors of radicalization, mental health issues, behaviors and offences. However, due to the predominantly descriptive analyses and the lack of generalizability, these results can only be considered as preliminary evidence for a criminology of sovereign citizens. Further empirical research is needed to better understand who sovereign citizens are, what their radicalization processes look like, and which factors can predict the use of violence. Only then can effective P/CVE measures be developed and adequately established.